Synthesis of ZnO Nanoparticle using Lidah Mertua (Sansevieria trifasciata) Extract through Sol-Gel Method and Its Application for Methylene Blue Photodegradation - Nanda Saridewi; Selviana Rustanti; Agustino Zulys; Siti Nurbayti; Isalmi Aziz; Adawiah Adawiah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Methylene blue is widely used in the textile industry and is difficult to degrade naturally because of its heterocyclic aromatic structure. One technique that can be used to degrade methylene blue is through a photocatalytic process using ZnO nanoparticles. This study aims to synthesize ZnO nanoparticles using Lidah mertua extract (Sansevieria trifasciata) as a capping agent by the sol-gel method, and determine the characteristics and stability of ZnO nanoparticles in methylene blue photodegradation. The synthesis of ZnO nanoparticles begins with drying Lidah mertua, grinding it, and then extracting it using distilled water. Furthermore, the extract was reacted with Zn(CH3COO)2.2H2O 0.15 M at pH 8. The extract was characterized using Fourier Transform Infrared (FTIR), and the ZnO nanoparticles were characterized using X-Ray Diffraction (XRD), ultraviolet-visible (UV-Vis) DRS, and Scanning Electron Microscopy (SEM). Lidah mertua extract has OH (hydroxyl), CN, CH, and C=C functional groups. The obtained ZnO nanoparticles have a crystal size of 19.324 nm. The crystalline phase is hexagonal; the morphology is spherical, with a particle size of 79.153 nm and a band gap energy of 3.21 eV. ZnO nanoparticles exhibited a methylene blue decolorization of 98.50% through 43.41% by adsorption and 55.09% by photocatalytic mechanism. ZnO nanoparticles showed good stability for a three-cycle reaction. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)